Correlation of interleukin 6 (IL-6) with estrogen and progesterone receptor expression in breast cancer patients - Chaloob, Amal K. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Multifunctional cytokines play important and only partially defined roles in mammary tumor development and progression. Normal human mammary epithelial cells constitutively produce interleukin 6(IL-6) and a non-secreted form of tumor necrosis factor. Transformation of mammary epithelial cells by different oncogenesis is frequently associated with alterations of cytokine/ growth factor production and responsiveness.Methods: We measured levels of 1L-6 in 84 females with breast cancer and examined their correlation with clinicopathological variables including stages of the disease and estrogen andprogesterone receptor expression on tumor cell.Results: Our results revealed significantly higher serum IL-6 in breast cancer patients (12.98 pg/ml) compared to a healthy group (2.05pg/ml) (P